1999
DOI: 10.1056/nejm199905133401902
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Margin Width on Local Control of Ductal Carcinoma in Situ of the Breast

Abstract: Postoperative radiation therapy did not lower the recurrence rate among patients with ductal carcinoma in situ that was excised with margins of 10 mm or more. Patients in whom the margin width is less than 1 mm can benefit from postoperative radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
321
1
18

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(354 citation statements)
references
References 35 publications
12
321
1
18
Order By: Relevance
“…This may explain why the 4-year local recurrence rates in the non-entered patients treated with LE+RT are relatively high compared to the patients in the trial treated with LE+RT. It might also indicate the importance of a complete excision, even with the application of RT (Silverstein et al, 1999;Bijker et al, 2001). In contrast, the non-entered patients treated with local excision alone had more similar 4-years local recurrence free rates in comparison to those patients treated with local excision in the trial, suggesting that LE alone is employed in those non-entered patients who were considered to have a low risk for local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why the 4-year local recurrence rates in the non-entered patients treated with LE+RT are relatively high compared to the patients in the trial treated with LE+RT. It might also indicate the importance of a complete excision, even with the application of RT (Silverstein et al, 1999;Bijker et al, 2001). In contrast, the non-entered patients treated with local excision alone had more similar 4-years local recurrence free rates in comparison to those patients treated with local excision in the trial, suggesting that LE alone is employed in those non-entered patients who were considered to have a low risk for local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…These are all based primarily on nuclear morphology and also, in some, on the presence or absence of necrosis or cell polarisation. The histological type, together with the lesion size, and, perhaps of most significance, the size of the margin of clearance have been found to be the best determinants of the risk of recurrence (Lagios et al, 1989;Poller and Ellis, 1995;Silverstein et al, 1996Silverstein et al, , 1999Bijker et al, 2001a;Douglas-Jones et al, 2002).…”
mentioning
confidence: 99%
“…This is the reason an adjuvant therapy was always added after surgery. A study by Silverstein et al21 had demonstrated that the likelihood of local recurrence in patients that were not treated with adjuvant radiotherapy decreased as tumor‐free surgical margin increased. Another study by Dunne et al demonstrated that a 2 mm margin was superior to a margin less than 2 mm, but there was no significant difference seen with a greater than 5 mm margin 22.…”
Section: Methodsmentioning
confidence: 99%
“…Also, a uniform cancer cell distribution seems unlikely given the clinical findings that the recurrence rate decreased with an increase in surgical margins and drastically declined at 2 mm margin 21, 22. In addition, a half‐Gaussian distribution is simple and it also follows the IB‐IORT dose fall‐off, therefore it is speculated that the cancer cell killing and normal tissue sparing would benefit from the IB‐IORT dose fall off with this pattern, since the region with the largest cancer cell burden will get the largest dose for intensive killing.…”
Section: Methodsmentioning
confidence: 99%